Pengaruh Money Saving, Time Saving, Pendapatan dan Lingkungan Sosial terhadap Keputusan Menggunakan Aplikasi Online Food pada Masyarakat Muslim di Kota Bekasi - M. Fadhli Nursal; Neng Siti Komariah; Muhammad Richo Rianto (Jurnal Ilmiah Ekonomi Islam, 2022)
This study examines the effects of money-saving, time-saving, income-saving, and social environment variables on decisions to use online food apps in Muslim communities in Bekasi City.The object of this quantitative design research is the entire Muslim community of Bekasi City who use online food applications. Purposive sampling was used in this study, with a total of 95 respondents. In this study, the analytical method was SmartPLS version 3.3. According to the findings of this study, the variables of money saving, time saving, and social environment influence the decision to use online food in Muslim communities in Bekasi City. While income has different results, income has no effect on the decision to use online food in Muslim communities in Bekasi City.This study also adds to the growing body of knowledge about the phenomenon of online food applications in an era of rapid technological advancement. This research can also be used as input and a summary of strategies that related parties can use to improve usage decisions.